2018
DOI: 10.1002/cbf.3361
|View full text |Cite
|
Sign up to set email alerts
|

SIX1 is upregulated in gastric cancer and regulates proliferation and invasion by targeting the ERK pathway and promoting epithelial‐mesenchymal transition

Abstract: Sine oculis homeobox homologue 1 (SIX1) is a Six class homeobox gene conserved throughout many species. It has been reported to act as an oncogene and is overexpressed in many cancers. However, the function and regulatory mechanism of SIX1 in gastric cancer (GC) remains unclear. In our study, we detected protein levels of SIX1 via immunohistochemistry (IHC) and its proliferation and invasion effects via CCK8 and transwell assays. Additionally, expression of cyclin D1, MMP2, p‐ERK, and EMT‐related proteins was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 35 publications
3
10
0
Order By: Relevance
“…Since epithelial-mesenchymal transition (EMT) is required for cell invasion involved in cancer progression [24,25], we investigated the expression of EMT markers following ZONAB up-regulation and found that ZONAB can down-regulate the expression of cytokeratin 8 and up-regulate the expression of vimentin, which is consistent with the result of Jiménez-Salazar and his colleague's study in breast cancer [50]. Our ndings demonstrate that ZONAB expression enhances epithelial-mesenchymal transition in bladder cancer.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Since epithelial-mesenchymal transition (EMT) is required for cell invasion involved in cancer progression [24,25], we investigated the expression of EMT markers following ZONAB up-regulation and found that ZONAB can down-regulate the expression of cytokeratin 8 and up-regulate the expression of vimentin, which is consistent with the result of Jiménez-Salazar and his colleague's study in breast cancer [50]. Our ndings demonstrate that ZONAB expression enhances epithelial-mesenchymal transition in bladder cancer.…”
Section: Discussionsupporting
confidence: 82%
“…us, the negative inhibitory e ect of ZONAB on E-cadherin expression suggests that up-regulation of ZONAB in bladder cancer enhances the invasive phenotype of bladder cancer. Epithelial-mesenchymal transition (EMT) is required for cell invasion involved in cancer progression [24,25]. To identify EMT following ZONAB up-regulation in bladder cancer, the expression of cytokeratin 8 as an epithelial marker and vimentin as a mesenchymal marker in xenogra tumor was detected by immunohistochemical staining.…”
Section: Zonab Down-regulation Attenuated Invasion Of Bladder Cancer mentioning
confidence: 99%
“…In addition, ENST00000575695.5 primarily regulated UBQLN1, which is linked with hypoxia responses in cells. Previous studies have also explored the roles of G6PC3, ATF6, BMP2, SIX1, RAB7A, and SOX2 in tumors [42][43][44][45][46][47] Together our results most clearly highlighted the importance of TEK, LDB2, ATF6 and UBQLN1 in NSCLC patient BE responses, underscoring the value of examining system-level gene interactions in order to better understand the determinants of lung cancer patient therapeutic responsiveness.…”
Section: Plos Onesupporting
confidence: 61%
“…19 In gastric cancer cells, SIX1 inhibits the mitochondrial apoptosis pathway via caspase-7, and it regulates proliferation and invasion by targeting the ERK pathway. 20,21 Liu et al 22 showed that SIX1 promotes tumor lymphangiogenesis via coordinating transforming growth factor b (TGF-b) signals that increase expression of vascular endothelial growth factor C (VEGF-C). In breast cancer, SIX1 overexpression reinstates an embryonic pathway of proliferation by upregulating cyclin A1 21 and mediates resistance to paclitaxel in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Liu et al 22 showed that SIX1 promotes tumor lymphangiogenesis via coordinating transforming growth factor b (TGF-b) signals that increase expression of vascular endothelial growth factor C (VEGF-C). In breast cancer, SIX1 overexpression reinstates an embryonic pathway of proliferation by upregulating cyclin A1 21 and mediates resistance to paclitaxel in breast cancer cells. 22 Moreover, multiple studies have demonstrated that high SIX1 expression leads to poor survival in a variety of cancers.…”
Section: Discussionmentioning
confidence: 99%